Roles of Sialic Acid, AXL, and MER Receptor Tyrosine Kinases in Mumps Virus Infection of Mouse Sertoli and Leydig Cells - Wang, Fei; Chen, Ran; Jiang, Qian; Wu, Han; Gong, Maolei; Liu, Weihua; Yu, Xiaoqin; Zhang, Wenjing; Han, Ruiqin; Liu, Aijie; Chen, Yongmei; Han, Daishu (Frontiers in Microbiology, 2020)
The mumps virus (MuV) causes epidemic parotitis. MuV also frequently infects the testis and induces orchitis, an important etiological factor contributing to male infertility. However, mechanisms underlying MuV infection of the testis remain unknown. Here, we describe that sialic acid, AXL and MER receptor tyrosine kinases regulate MuV entry and replication in mouse major testicular cells, including Sertoli and Leydig cells. Sialic acid, AXL and MER were present in Sertoli and Leydig cells. Sialic acid specifically mediated MuV entry into Sertoli and Leydig cells, whereas both AXL and MER facilitated MuV replication within cells through the inhibition of cellular innate antiviral responses. Mechanistically, the inhibition of type 1 interferon signaling by AXL and MER is essential for MuV replication in Sertoli and Leydig cells. Our findings provide novel insights into the mechanisms behind MuV infection and replication in the testis.